Side loads and thermal loads in rocket nozzles. Overview of the CNES-ONERA ATAC programme. (2nd March 2011) - Reijasse, Philippe; Palerm, Sandrine; Pouffary, Benoit
The ATAC group was created in the late 1990s on CNES and ONERA's initiative, and in cooperation with French laboratories and industrials, to investigate aerodynamics issues for space launchers nozzles and blunt bodies. This paper presents a synthesis of the research work done in the frame of the ATAC programme to better understand the flow separation phenomenon in over expanded nozzles.